Maintenance treatment in non-small cell lung cancer (NSCLC): pro - Mazzoni, Francesca; Lunghi, Alice; Petreni, Paolo; Vannini, Agnese; Pellegrini, Elisa; Cecere, Fabiana Letizia; Di Costanzo, Francesco (European Journal of Oncology and Environmental Health, 2015)
Non-small cell lung cancer (NSCLC) is the second tumor in incidence worldwide and, at present, remains the leading cause of cancer death. According to the Italian Drug governance, although the incoming knowledge reached during these years, the backbone treatment of the advanced stages of lung cancer remains standard chemotherapy. Platinum-based chemotherapy, prolonged from four to six cycles, is the standard therapy for all the subtypes of NSCLC without Epidermal Growth Factor Receptor (EGFR) mutation. According to the several guidelines, second line therapy must be composed by a single agent drug. During recent years a great attention has been given to the chemotherapy free window which existed between the first and the second line, in case of stable disease (SD) or objective response (OR). Several therapeutic maintenance strategies have been studied, both in continuing the strategy chosen for the first line and in changing the drug, with a no cross-resistant agent, stopping the platinum salt anyway. Although a number of these studies demonstrated that maintenance therapy improved progression free survival (PFS) compared with observation, only few had a significant overall survival (OS) benefit. Pemetrexed, utilized both in patients treated with this drug in first line and as switch maintenance, and bevacizumab, in continuation maintenance setting, are the only drugs which have been shown able to prolong OS in adenocarcinoma histology. Despite these positive results, implementation of maintenance therapy in NSCLC remains debated, and at this moment there are no data comparing continuation and switch maintenance treatment.